Long-term outcome of endoscopic resection for intramucosal esophageal squamous cell cancer: a secondary analysis of the Japan Esophageal Cohort study - Oda, Ichiro; Shimizu, Yuichi; Yoshio, Toshiyuki; Katada, Chikatoshi; Yokoyama, Tetsuji; Yano, Tomonori; Suzuki, Haruhisa; Abiko, Satoshi; Takemura, Kenichi; Koike, Tomoyuki; Takizawa, Kohei; Hirao, Motohiro; Okada, Hiroyuki; Yoshii, Takako; Katagiri, Atsushi; Yamanouchi, Takenori; Matsuo, Yasumasa; Kawakubo, Hirofumi; Kobayashi, Nozomu; Shimoda, Tadakazu; Ochiai, Atsushi; Ishikawa, Hideki; Yokoyama, Akira; Muto, Manabu (Endoscopy, 2020)
Background Prospectively collected long-term data of patients undergoing endoscopic resection for superficial esophageal squamous cell carcinoma (ESCC) are limited. The aim of this study was to determine the prospectively collected long-term outcomes of endoscopic resection for ESCC as a secondary analysis of the Japan Esophageal Cohort (JEC) study.Methods Patients who underwent endoscopic resection of intramucosal ESCC at 16 institutions between September 2005 and May 2010 were enrolled in the JEC study. All patients underwent endoscopic examination with iodine staining at 3 and 6 months after resection, and every 6 months thereafter. We investigated clinical courses after endoscopic resection, survival rates, and cumulative incidence of metachronous ESCC.Results 330 patients (mean age 67.0 years) with 396 lesions (mean size 20.4 mm) were included in the analysis. Lesions were diagnosed as high-grade intraepithelial neoplasia in 17.4 % and as squamous cell carcinoma in 82.6 % (limited to epithelium in 28.4 %, to lamina propria in 55.4 %, and to muscularis mucosa in 16.2 %). En bloc resection was achieved in 291 (73.5 %). The median follow-up period was 49.4 months. Local recurrences occurred in 13 patients (3.9 %) and were treated by endoscopic procedures. Lymph node metastasis occurred in two patients (0.6 %) after endoscopic resection. The 5-year overall, disease-specific, and metastasis-free survival rates were 95.1 %, 99.1 %, and 94.6 %, respectively. The 5-year cumulative incidence rate of metachronous ESCC was 25.7 %.Conclusions Our study demonstrated that endoscopic resection is an effective treatment for intramucosal ESCC, with favorable long-term outcomes.